2017
DOI: 10.3390/su9112092
|View full text |Cite
|
Sign up to set email alerts
|

Social Life Cycle Assessment in the Textile Sector: An Italian Case Study

Abstract: This study presents the first application of the Social Life Cycle Assessment (S-LCA) to a textile product made in Sicily (Italy), according to the Social Life Cycle Assessment guidelines (UNEP). The main goal is to assess and present the social values of a product manufactured in a particular territorial area where the presence of an industry represents the main source of employment. The first part of the study is a literature review of the current state of the art of the S-LCA and its implementation to texti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…It was difficult to evaluate how the company motivates its suppliers to meet the basic requirement (BR) introduced in SAM. This is in line with the study conducted by Lenzo et al (2017) who also found similar results in their case studies within the textile sector in Italy, highlighting the lack of data availability for proving the company actions in promoting the BR of the indicators among its suppliers. As mentioned by Parent et al (2013), if suppliers need to enhance their social performance, a competitive benefit is necessary so that they are encouraged to perform better.…”
Section: Interpretation Of the Resultssupporting
confidence: 89%
“…It was difficult to evaluate how the company motivates its suppliers to meet the basic requirement (BR) introduced in SAM. This is in line with the study conducted by Lenzo et al (2017) who also found similar results in their case studies within the textile sector in Italy, highlighting the lack of data availability for proving the company actions in promoting the BR of the indicators among its suppliers. As mentioned by Parent et al (2013), if suppliers need to enhance their social performance, a competitive benefit is necessary so that they are encouraged to perform better.…”
Section: Interpretation Of the Resultssupporting
confidence: 89%
“…Innovative demand-side measures can complement existing malaria control interventions such as insecticide-treated mosquito nets (ITN) and artemisininbased combination therapies (ACT), in that they can be effective in regulating and curtailing demand for internationally traded malaria-implicated commodities such as timber, soy, beef, and palm oil. Some demand-side measures already exist for mitigating biodiversity threats 36 , child labour 40 , and global inequality 41 .…”
mentioning
confidence: 99%
“…Social LCA (S-LCA) follows a similar cradle-to-grave approach as environmental LCA, but its focus is on social aspects related to the quality of life and wellbeing of all categories of stakeholders involved in the processes under review. S-LCA inventories range from child labour to freedom of association, from cultural heritage to access to intangible resources, from gender discrimination to health and safety and from indigenous rights to corruption [37]. Benefits from Social LCA are detailed knowledge about social and wellbeing impacts generated by a process, in a framework that is very close to the sustainable Development Goals of United Nations and to the ISO 26000 standard regarding Corporate Social Responsibility [38].…”
Section: Social Lcamentioning
confidence: 99%